2012
DOI: 10.3174/ajnr.a2911
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Protected Carotid Artery Stenting in Patients with Severe Carotid Artery Stenosis and Carotid Intraplaque Hemorrhage

Abstract: BACKGROUND AND PURPOSE:Carotid IPH can be detected with MR imaging. The aim of this study was to determine the safety of CAS using an emboli protection device in patients with severe carotid artery stenosis and MR imaging-depicted carotid IPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…In our study, the composite rate of 30-day stroke (minor or major), myocardial infarction, and death was 3.9%, which is lower than that of the Carotid Revascularization Endarterectomy vs. Stenting Trial (CREST) trial. We also found no significant difference in primary outcomes after CAS between symptomatic and asymptomatic patients, which were consistent with findings of a similar, previous study (19).…”
Section: Outcome Based On Carotid Hr-mri Findingssupporting
confidence: 82%
See 2 more Smart Citations
“…In our study, the composite rate of 30-day stroke (minor or major), myocardial infarction, and death was 3.9%, which is lower than that of the Carotid Revascularization Endarterectomy vs. Stenting Trial (CREST) trial. We also found no significant difference in primary outcomes after CAS between symptomatic and asymptomatic patients, which were consistent with findings of a similar, previous study (19).…”
Section: Outcome Based On Carotid Hr-mri Findingssupporting
confidence: 82%
“…However, Yoon et al (19) suggested that protected CAS is safe in patients with severe carotid stenosis and IPH. In a previous study from our group (20), we reported that IPH is not a significant risk factor for cerebral embolism during CAS in patients with severe carotid artery stenosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include conventional T1-weighted fast spin echo, TOF MRA, or MPRAGE sequences. Several studies have used TOF sequencing to detect carotid IPH, and a routine MRA protocol without additional sequences to evaluate carotid atherosclerosis (1,5,9,15). The appearance of a halo sign around the carotid artery on the MIP of the TOF MRA was useful for the noninvasive detection of a fresh or recent carotid IPH on histologic analysis (6,9).…”
Section: Discussionmentioning
confidence: 99%
“…The three T1-weighted sequences were two-dimensional (2D) fast spin-echo, three-dimensional (3D) time-of-flight (TOF), and threedimensional magnetization-prepared rapid acquisition gradient-echo (MPRAGE) sequence for detecting or quantifying IPH (1,(5)(6)(7)(8). Ota et al (8) reported on the diagnostic performance of three T1-weighted 3.0-T MR sequences at carotid IPH imaging, using histologic analysis as the standard of reference.…”
Section: Introductionmentioning
confidence: 99%